Peran Seni dalam Pengajaran - Ardipal Ardipal (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2008)
This article is aimed at finding out  the role of art in a language teaching. The data were gathered through library research, observation, and interviews with art practitioners concerning the role and the influence of art in human life as viewed from its characteristics.  The research shows that art has a role in shaping behavior and developing multi-intelligence. In conclusion, art has contributed to all aspects of life including a language teaching. In this case, art has contributed in improving the ability to manage teaching learning process and helping the learners to actualize various potential abilities they have. Key words: art, art role, language teaching